Coming of age in contemporary American fiction - Millard, Kenneth (Edinburgh University Press, 2007)
This book explores the ways in which a range of recent American novelists have handled the genre of the 'coming-of-age' novel, or the Bildungsroman. Novels of this genre characteristically dramatise the vicissitudes of growing up and the trials and tribulations of young adulthood, often presented through depictions of immediate family relationships and other social structures. This book considers a variety of different American cultures (in terms of race, class and gender) and a range of contemporary coming-of-age novels, so that aesthetic judgements about the fiction might be made in the context of the social history that fiction represents. A series of questions are asked: Does the coming-of-age moment in these novels coincide with an interpretation of the 'fall' of America? What kind of national commentary does it therefore facilitate? Is the Bildungsroman a quintessentially American genre? What can it usefully tell us about contemporary American culture? Although the focus is on the contemporary period, this is placed in the context of reference to earlier novels and criticism of the genre, as well as historical changes in the status of the family, and the adolescent within it. Key Features. Provides detailed interpretations of 12 key contemporary novels from authors including Purple America by Rick Moody, The Age of Consent by Geoffrey Wolff, The Virgin Suicides by Jefffrey Eugenides and Prozac Nation by Elizabeth Wurtzel. Explains the importance of the coming-of-age genre to the broader American literature canon. Makes a significant intervention in contemporary debate about what is most valuable in recent American fiction.